Colombia's displaced indigenous women - Escobar Cuero, G (Refugee Studies Centre, University of Oxford, 2017)
Indigenous peoples are one of the most vulnerable groups within Colombia’s internally displaced population, and a lack of understanding of their culture and needs constitutes a major challenge to their protection and assistance.